Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/ofid/ofz360.1193
|View full text |Cite
|
Sign up to set email alerts
|

1329. Experiences and Emotional Challenges of Antiretroviral Treatment (ART)—Findings from the Positive Perspectives Study

Abstract: BackgroundWhile advances in treatment have dramatically improved the lives of people living with HIV (PLHIV), a number of important unmet needs remain. We conducted an international survey of PLHIV to explore their treatment experience and emotional challenges of ART.MethodsQualitative in-depth interviews were performed with PLHIV to identify key hypotheses. A steering group (led by community members) developed the survey tool which was fielded online from November 2016 to July 2017 in 8 high-income countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Some populations of PLWH may therefore find this a preferable option to their daily CAR, potentially facilitating improved adherence in those who report factors such as pill burden and forgetfulness as barriers to adherence. 4 The Positive Perspectives study involving over 1000 PLWH found that most regarded daily ART as a “reminder of their HIV status,” whereas 25% felt “being tied to daily medication limited their day to day life.” 7 Monthly CAB + RPV LA injections may therefore represent a more discreet regimen that could help some PLWH avoid the stigma associated with their HIV status. CAB + RPV LA would also enable the first option for directly observed therapy because of the monthly clinic visits required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some populations of PLWH may therefore find this a preferable option to their daily CAR, potentially facilitating improved adherence in those who report factors such as pill burden and forgetfulness as barriers to adherence. 4 The Positive Perspectives study involving over 1000 PLWH found that most regarded daily ART as a “reminder of their HIV status,” whereas 25% felt “being tied to daily medication limited their day to day life.” 7 Monthly CAB + RPV LA injections may therefore represent a more discreet regimen that could help some PLWH avoid the stigma associated with their HIV status. CAB + RPV LA would also enable the first option for directly observed therapy because of the monthly clinic visits required.…”
Section: Discussionmentioning
confidence: 99%
“… 4 6 Furthermore, the emotional burden of living with HIV may be compounded by daily oral pill taking and additional complexities. 7 Therefore, there is considerable interest in developing long-acting (LA) treatments that can address many of these issues while simplifying ART for PLWH. 8 …”
Section: Introductionmentioning
confidence: 99%
“…This has culminated in the development of efficacious single-tablet daily oral regimens, which offer simplicity and convenience [3]. Despite this, the need for life-long daily pill-taking can present substantial challenges that can be broadly grouped into three categories: adherence issues [4]; emotional issues, including stigmatization concerns and the daily reminder of HIV status [5]; and medical issues, such as difficulty swallowing, drug-food and drug-drug interactions, and pill burden [6]. These challenges can impact the likelihood of treatment failure, with poor adherence to antiretroviral therapy linked to the emergence of resistance and virologic failure [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We found that about three quarters of the participants reported inconvenience in daily life due to ART use, and this was a predictor of moderate/severe anxiety. Taking ART every day may be a reminder of their HIV status and make them feel stressed [35]. Scaling up the single tablet regimen and reducing dose frequency could thus help to improve mental health among PLWH on ART.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the daily regimen of ART is inconvenient for PLWH. For example, 25% of PLWH in eight high-income countries agreed that being tied to daily medication limited their day-to-day life, and 29% felt stressed by the need to take their medication at the right time every day [35]. These experiences related to ART may also in uence mental health among PLWH.…”
mentioning
confidence: 99%